Reflexión en torno al tema de derecho y economía: Su encuadre en la corriente institucional y neoinstitucional - Romero-Pérez, Jorge Enrique (2014)
This approach and method disseminated as Economic Analysis of Law derives from the Anglo-Saxon culture, where it is known as Law and Economics. It deals with the application of the economic theory to the field of the economic processes and impacts of Law and juridical institutions.